Component Analysis of Bee Venom from lune to September - Ki Rok Kwon; Ching Seng Chu; Jang Ho Lee; Min Ki Kim; Bae Chun Cha (Korean Pharmacopuncture Institute, 2007)
Objectives : The aim of this study was to observe variation of Bee Venom content from the collection period. Methods : Content analysis of Bee Venom was rendered using HPLC method by standard melittin Results : Analyzing melittin content using HPLC, 478.97mg/g at june , 493.89mg/g at july, 468.18mg/g at August and 482.15mg/g was containing in Bee Venom at september. So the change of melittin contents was no significance from June to September. Conclusion : Above these results, we concluded carefully that collecting time was not important factor for the quality control of Bee Venom, restricted the period from June to September.